RcsB regulation of the YfdX-mediated acid stress response in Klebsiella pneumoniae CG43S3. - Chia-Jui Liu; Ching-Ting Lin; Jo-Di Chiang; Chen-Yi Lin; Yen-Xi Tay; Li-Cheng Fan; Kuan-Nan Peng; Chih-Huan Lin; Hwei-Ling Peng (PLoS ONE, 2019)
In Klebsiella pneumoniae CG43S3, deletion of the response regulator gene rcsB reduced the capsular polysaccharide amount and survival on exposure to acid stress. A comparison of the pH 4.4-induced proteomes between CG43S3 and CG43S3ΔrcsB revealed numerous differentially expressed proteins and one of them, YfdX, which has recently been reported as a periplasmic protein, was absent in CG43S3ΔrcsB. Acid survival analysis was then conducted to determine its role in the acid stress response. Deletion of yfdX increased the sensitivity of K. pneumoniae CG43S3 to a pH of 2.5, and transforming the mutant with a plasmid carrying yfdX restored the acid resistance (AR) levels. In addition, the effect of yfdX deletion was cross-complemented by the expression of the periplasmic chaperone HdeA. Furthermore, the purified recombinant protein YfdX reduced the acid-induced protein aggregation, suggesting that YfdX as well as HdeA functions as a chaperone. The following promoter activity measurement revealed that rcsB deletion reduced the expression of yfdX after the bacteria were subjected to pH 4.4 adaptation. Western blot analysis also revealed that YfdX production was inhibited by rcsB deletion and only the plasmid expressing RcsB or the nonphosphorylated form of RcsB, RcsBD56A, could restore the YfdX production, and the RcsB-mediated complementation was no longer observed when the sensor kinase RcsD gene was deleted. In conclusion, this is the first study demonstrating that YfdX may be involved in the acid stress response as a periplasmic chaperone and that RcsB positively regulates the acid stress response partly through activation of yfdX expression. Moreover, the phosphorylation status of RcsB may affect the YfdX expression under acidic conditions.